2006
DOI: 10.1111/j.1750-3841.2006.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 50% Ethanol Extract from Rosemary (Rosmarinus officinalis) on α‐Glucosidase Inhibitory Activity and the Elevation of Plasma Glucose Level in Rats, and Its Active Compound

Abstract: Rosemary (Rosmarinus officinalis) extract with 50% ethanol remarkably inhibited rat intestinal αglucosidase (sucrase) activity when compared with 31 different herbs and spices (aqueous and 50% ethanol aqueous extracts). Rosemary-distilled extract obtained from 50% ethanol extract by evaporation inhibited α-glucosidase activity in the reaction with both maltose and sucrose. Maltose or sucrose was orally administered, with or without rosemary-distilled extract, to mice at a dose of 20 mg/mouse. A postprandial el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…10 Schematic overview of the mechanism of action of rosmarinic acid during HFD-STZ-induced experimental diabetes mellitus in rats the condition which is reversed upon oral administration of RA. These data indicate the beneficial effects of RA in preventing the diabetic complications which is supported by the previous studies which demonstrates that RA extract regulates glucose metabolism in rats [49].…”
Section: Nrf-2supporting
confidence: 80%
“…10 Schematic overview of the mechanism of action of rosmarinic acid during HFD-STZ-induced experimental diabetes mellitus in rats the condition which is reversed upon oral administration of RA. These data indicate the beneficial effects of RA in preventing the diabetic complications which is supported by the previous studies which demonstrates that RA extract regulates glucose metabolism in rats [49].…”
Section: Nrf-2supporting
confidence: 80%
“…Moreover, recent study reported that rosemary leaves lead to regeneration of the b-cells of the pancreas and potentiating of insulin secretion from surviving b-cells, which indicates that rosemary leaves decrease blood glucose level by stimulating insulin secretion from the remnant b-cells or regenerated b-cells (Alnahdi, 2012). Furthermore, the reduction of fasting blood glucose may be due to that rosemary leaves might inhibit the intestinal absorption of glucose by inhibition of intestinal amylase enzyme or a-glucosidase enzyme (McCue and Shetty, 2004;Koga et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…by the inhibition of endogenous glucose production (Eddouks et al, 2003) or by the inhibition of intestinal glucose absorption (Platel and Srinivasan, 1997). In a previous study, it has been suggested that 50% ethanol extract of Rosmarinus officinalis, in part, due to intestinal ␣-glucosidase (AGc) inhibitory activity of its active compound might play a role in controlling dietary glucose uptake in the small intestinal track (Koga et al, 2006).…”
Section: Discussionmentioning
confidence: 99%